Antibiofilm efficacy of novel biogenic silver nanoparticles from Terminalia catappa against food-borne Listeria monocytogenes ATCC 15,313 and mechanisms investigation in-vivo and in-vitro - Lakshmanan Muthulakshmi; Kannan Suganya; Maruthamuthu Murugan; Jamespandi Annaraj; Veeramuthu Duraipandiyan; Dunia A. Al Farraj; Mohamed S. Elshikh; Annie Juliet; Mukesh Pasupuleti; Jesu Arockiaraj (Journal of King Saud University: Science, 2022)
Listeria monocytogenes (LM) is a potential foodborne pathogen, known to form biofilms, which ultimately leads to serious problems in the food industry. This study demonstrates a comprehensive approach for the synthesis of silver nanoparticles using the phytochemicals present in the leaf aqueous extract of Terminalia catappa for the inhibition of L. monocytogens biofilms. The phytochemical analysis by UV–vis spectrum of the extract revealed the presence of polyphenolic compounds such as ellagic acid, gallic acid, chebulinic acid, and chebulgic acid. The shape, structure and size of the synthesized AgNPs were determined as 23–100 nm using the scanning electron microscopic images, and particle size distribution curve analysis. The in vitro studies using the AgNPs against L. monocytogenes revealed the inhibition of biofilm formation, reduction in the Virulence factors such as protease production at sub-inhibitory concentrations of AgNPs. In vivo experiments performed with the Caenorhabditis elegans model showed that AgNPs prolonged the lifespan of infected worms by about 90%. In addition, the non-hazardous nature and in vivo anti-adherence potential of AgNPs were also established with LM - C. elegans infection model.